Physical activity and functional social support in community-dwelling older adults: a scoping review - Paula Steinhoff; Amelie Reiner (BMC, 2024)
Abstract Background Globally, the population of older people is increasing and is estimated to reach nearly 2.1 billion by 2050. Physical activity (PA) is one of the key components for successful ageing. However, PA decreases with age and many older adults do not meet PA guidelines. Previous research has shown that social support (SOSU) is related to PA in older people. The aim of this scoping review is to identify and map all of the available evidence and to explore the association between functional SOSU and PA in older adults. Functional SOSU consists of emotional, informational, instrumental and companionship SOSU and social comparison. Methods A scoping review was conducted using the Joanna-Briggs manual. Quantitative and qualitative studies investigating associations between functional SOSU and PA levels in older adults (mean age ≥ 60 years) were identified through a systematic search in seven electronic databases up to August 2023. After removing duplicates, 20,907 articles were screened for titles and abstracts. The results were analysed separately for different types of SOSU. Results 116 articles met the inclusion criteria; 72% were quantitative studies and 28% were qualitative studies. Most studies used self-reported PA measures, only 23% of the studies used objective-reported PA measures. Most studies of SOSU for PA reported positive associations but the evidence is inconclusive when the source of support is considered. PA is positively associated with general, emotional, informational, and companionship SOSU, while instrumental support may occasionally be negatively associated. Companionship support is particularly influential on PA, especially in group settings, as it promotes social connectedness. Qualitative studies show that social comparison also supports PA. Different forms of SOSU generally show positive associations with PA. Conclusions While the evidence on the association between functional SOSU and PA is mixed, most studies show that there is a positive association. PA may also be a strategy for improving social contact and social integration. This study offers a comprehensive overview of measures for SOSU and PA and thereby informs future research and policy-making.